The role of catholic faith on health - post-pandemic: theological reflection - Suwito, Benny (Technium Social Sciences Journal, 2024)
Health is one of the main elements in human life. Everyone always gives ample space for their health. However, sometimes people forget this when their life goals are not well understood or are limited to certain achievements. This scientific work examines the reinterpretation of the Catholic faith as a search for human nature and how the Catholic faith and health are actually an inseparable unity because humans are complete creatures. Apart from that, this scientific work also reflects the ideal human attitude in facing crises, especially health crises in the new post-pandemic era, namely "Being human also means being a healthy human being" because humans who are able to find faith can understand it. the importance of health in their lives. For those who understand the integral relationship between the Catholic faith and health, this provides confirmation of the true dignity of human beings, including their relationship to "the Divine."